Prenatal exposure to permethrin influences vascular development of fetal brain and adult behavior in mice offspring. Issue 11 (24th August 2011) - Imanishi, Satoshi; Okura, Masahiro; Zaha, Hiroko; Yamamoto, Toshifumi; Akanuma, Hiromi; Nagano, Reiko; Shiraishi, Hiroaki; Fujimaki, Hidekazu; Sone, Hideko
<x xml:space="preserve">Abstract</x> Pyrethroids are one of the most widely used classes of insecticides and show neurotoxic effects that induce oxidative stress in the neonatal rat brain. However, little is still known about effects of prenatal exposure to permethrin on vascular development in fetal brain, central nervous system development, and adult offspring behaviors. In this study, the effects of prenatal exposure to permethrin on the development of cerebral arteries in fetal brains, neurotransmitter in neonatal brains, and locomotor activities in offspring mice were investigated. Permethrin (0, 2, 10, 50, and 75 mg/kg) was orally administered to pregnant females once on gestation day 10.5. The brains of permethrin‐treated fetuses showed altered vascular formation involving shortened lengths of vessels, an increased number of small branches, and, in some cases, insufficient fusion of the anterior communicating arteries in the area of circle of Willis. The prenatal exposure to permethrin altered neocortical and hippocampus thickness in the mid brain and significantly increased norepinephrine and dopamine levels at postnatal day 7 mice. For spontaneous behavior, the standing ability test using a viewing jar and open‐field tests showed significant decrease of the standing ability and locomotor activity in male mice at 8 or 12 weeks of age, respectively. The results suggest that prenatal exposure to permethrin may affect insufficient development of the brain through alterations of vascular development. © 2011 Wiley Periodicals, Inc. Environ Toxicol 28:617–629, 2013.